Integrating spatial dynamics for sustainable water management at the river basin scale: the example of the Krishna River Basin in South India - Venot, Jean-Philippe (2007)
The Krishna Basin in South India has seen an increasing agricultural and water development since India gained independence. This has resulted in over-commitment of water: more water is used than is environmentally desirable or than is renewably available, leading to basin closure (zero or minimal flow to the ocean). As basin closure intensifies the interconnectedness of ecosystems and water users, adjustments and management decisions become tantamount to a spatial re-appropriation of water. Acknowledging and integrating these spatial dynamics of water availability and use is needed to avoid social and environmental impacts. This can only be achieved through a multilevel governance structure centered on basin-wide strategies of water management. Basin water management would then start with the definition and the implementation of water allocation mechanisms that are increasingly needed to ensure a balance between equity, sustainability and efficient uses of scarce water resources for both human benefit and environment preservation.